Characteristics and dynamic significance of the structural stress field in the central segment of the Tan-Lu Fault Zone and its adjacent areas - JiaJi Luo; ZheMin Liu; ShuYuan Yu; Bing Feng; ZheJun Li; Peng Zhao; YuanYuan Yang (Earth and Planetary Physics, 2025)
This article presents an interpretation of the seismic source mechanisms for 905 earthquakes with MS > 2.0, occurring in the central and southern sections of the Tan-Lu Fault Zone and its adjacent areas from 1970 to 2023. Utilizing the damped stress tensor method, we have inverted the spatial characteristics of the stress field variations in this study area, at a resolution of 1.0° × 1.0°. The results indicate that the maximum principal stress direction within the central and southern sections of the Tan-Lu Fault Zone exhibits a spatially continuous change, rotating counterclockwise from East-West (EW) to Northeast-East (NEE), albeit with local variations. When dividing along the Tan-Lu Fault Zone, it is observed that on its western side — the North China block — a near EW stress field predominates. In contrast, on its eastern side — the Ludong-Huanghai Block — stress fields primarily exhibit NEE and Northeast-East (NE) orientations, underscoring the role of the Tan-Lu Fault Zone as a significant boundary between tectonic blocks. In regions located between latitudes 30°−34°N and longitudes 113°−115°E on the western side of these fault zone sections, maximum principal stress follows a radial distribution pattern indicative of a complex stress field. Conversely, on the eastern side of this fault zone, maximum principal stress direction remains relatively consistent, primarily displaying NEE and NE distributions. This reflects the fact that this area is situated under a tectonic background characterized by near NEE-NE direction for the Ludong−Huanghai Block. However, within an area bounded by latitudes 30°−32°N and longitudes 120°−122°E on the eastern flank of the Tan-Lu Fault Zone, maximum principal stress direction appears more intricate, with radial distribution patterns suggesting influences not only from near EW-NEE movements associated with the North China Block, but also from westward subduction processes related to Philippine Sea plate dynamics. Through our analysis of historical earthquakes in this region, we conclude that the moderate to strong seismic activity within this area is significantly related to the tectonic stress environment, with regions of complex tectonic stress often being the most seismically active.